Sustainable oral hygiene products and practices: Perspectives, expectations, and barriers of portuguese residents - Cleuzilena Barros; Cristina Bettencourt Neves; Sónia Mendes (Sociedade Portuguesa de Estomatologia e Medicina Dentária, 2023)
Objectives: In recent decades, there has been a growing awareness of the impact of daily practices on the environment and a greater concern of companies to develop sustainable products; consequently, a wide variety of sustainable oral hygiene products is available. The study aims to analyze the consumer's perspective regarding the use of sustainable products for oral health self-care, namely practices, opinions, and difficulties felt regarding the use of these products. Methods: A cross-sectional study was carried out on individuals 18 years old or older living in Portugal. Data were obtained through an online questionnaire, which collected information on the use of sustainable oral hygiene products, practices, perceptions, and difficulties experienced in adopting a sustainable lifestyle. Descriptive statistics were performed for the variables. Results: The sample consisted of 185 participants. The majority (64.3%) considered it "very important" to invest in developing sustainable oral hygiene products. However, only 37.3% reported having already used these products. Of these, most were satisfied or very satisfied with the sustainable products used. Personal lack of interest (93.0%), difficulty in accessing products in commercial establishments (69.2%), and the high price of products (61.1%) were the main difficulties experienced in using these products. Conclusions: Participants were aware of more sustainable oral hygiene products, but there is still a low frequency of use. It would be important to study the efficacy and safety of these products to promote the use of more environmentally friendly oral hygiene products.